Self-Assessment Towards Continuous Professional Development of Islamic Education Teachers: A Research Approach Using Mixed Methods - Masuwai, Azwani; Zulkifli, Hafizhah; Isa Hamzah, Mohd (International Journal of Psychosocial Rehabilitation, 2024)
The study aimed to understand the mixed-method approach as a research design for self-assessment study of Islamic Education Teachers (IET) towards Continuous Professional Development. The selection of this method was based on the needs of the study that required for researcher to get a real picture of the concept of self-assessment among IETs from the view of individuals with well experience in this field. The level of self-assessment practice will be taken for the next stage of the study. This type of mixed method known as exploratory sequential design that began with a qualitative approach and followed with a quantitative approach. The findings of interview with six experienced Islamic Education experts who were selected based on certain criteria used as a basis for the questionnaire instrument development that later used to obtain further quantitative data for this study. This article stressed the importance of the selection of this method by looking at the needs and how the data from the two methods can be connected to answer the research objective of the study.